Is the system of rice intensification (SRI) consonant with agroecology?. Issue 10 (25th November 2020) - Deb, Debal
ABSTRACT: A large body of evidence indicates that SRI can enhance rice grain yield with substantially less water input than in conventional indsutrialized rice farms. While SRI conserves a large amount of water, it tends to endorse rice monocultures and emphasize complete eradication of weeds – practices that drastically truncate farm biodiversity. Except for a subset of "organic SRI, " most SRI practitioners apply agrochemicals. SRI proponents recommend the use of cono weeder, for weeding and soil aeration. However, poor farmers find the machine to be too costly and tend to apply herbicides for weed control, to the detriment of the environment and human health. In areas where surface water is unavailable, SRI induces use of pumps, which deplete groundwater stock and emit greenhouse gases, albeit substantially less in quantity than in conventional farming. Farmers' adoption of SRI is motivated by spectacular grain yield, while environmental benefits remain a secondary consideration. This paper examines the SRI components that are discordant with the principles of agroecology and recommends redesigning of SRI methodology to conform to agroecology.